The New Principle-practice Gap: The Disconnect between Diversity Beliefs and Actions in the Workplace. Issue 2 (April 2022) - Bowman Williams, Jamillah; Cox, Jonathan M.
Following increased calls for racial justice, many organizations have pledged to play their part in dismantling systemic racism. One common step leaders take is to invest in diversity and inclusion programs. Yet, despite organizations' bold claims to value diversity and the investment of billions of dollars on related efforts, workplace discrimination continues to be a major factor in the lives of people of color. In addition, existing research highlights a principle-policy gap, wherein people—particularly White Americans—espouse support for the principles of diversity, yet their support wanes for policies that address inequalities. In this survey study, we explore attitudes about organizational diversity efforts and further examine how these beliefs shape workplace decision making. Our analysis of open-ended responses reveals a major disconnect, where individuals say diversity is important in principle, yet in practice do not take actions to further the goals of diversity and inclusion programs, a phenomenon we label the "principle-practice gap." We use diversity ideology as the theoretical link to help explain why this subtle resistance to action might occur. We find that the principle-practice gap is more pronounced for those who view diversity as important because it improves outcomes. Conversely, those who think diversity is an important goal because of workplace inequality are more likely to take action, such as promoting a Black man. These findings help reveal which people endorsing diversity in principle are more likely to take action and which tend to be more performative and less connected to practices that counter structural inequality.